(untitled) (Journal of Fiber Bioengineering and Informatics, 2013)
A systems approach that integrates processing, structure, property and performance relations has been used in the design of multilevel-structured fibrous materials. For electrospun fibrous structure, numerical implementation of multiscale materials philosophy provides a hierarchy of computational models defining design parameters that are integrated through computational continuum mechanics. Electrospun micro/nano (multiscale) poly(ε-caprolactone) (PCL) fibrous scaffolds were studied. The fibrous structures were evaluated for their mechanical, morphological and cell attachment properties. The cell attachment studies showed that cell activity on multi-scale scaffolds was higher compared to micro-fibrous scaffolds. These results suggest that the combination of a micro- and nano-fiber hierarchical scaffold could be more beneficial for tissue engineering applications than for individual scaffolds.